TINGKAT PENGETAHUAN MAHASISWI TENTANG KANKER PAYUDARA DI APIKES CITRA MEDIKA SURAKARTA - Ikrima Rahmasari; Rahayu Kurniadew; Liss Dyah Dewi Arini (Universitas Duta Bangsa Surakarta, 2021)
Introduction: Cancer is one type of disease that is feared by many people in the world so it is better to prevent it. The results of the preliminary study after being asked questions to 10 female students about breast cancer showed that 6 female students knew about the definition of breast cancer, and how to detect it early and 4 other female students only knew about the definition of breast cancer. Objective: to determine the level of knowledge of female students about breast cancer at APIKES Citra Medika Surakarta. Methods: Using quantitative descriptive, the population is all female students of APIKES Citra Medika Surakarta obtained 87 respondents, the sampling technique uses probability sampling by simple random sampling, the research instrument uses a closed questionnaire and uses univariate analysis. Results: The level of knowledge about breast cancer is good, there are 50 respondents (57.5%), 29 respondents (33.3%), and 8 respondents (9.2%) have less knowledge. Conclusion: The level of knowledge about breast cancer is good, sufficient and lacking.